Third time's a charm: diagnosis of herpes simplex encephalitis after two negative polymerase chain reaction results. Issue 6 (June 2020) - Niksefat, Mahbobeh; Guillen, Daniel; Moshayedi, Pouria; Rinaldo, Charles R.; Ojha, Ajitesh
Abstract: Introduction: Polymerase chain reaction (PCR) testing of cerebrospinal fluid (CSF) is a sensitive and specific method in diagnosing herpes simplex virus (HSV) encephalitis. However there are increasing reports of false negative HSV PCR. Case description: We present a patient in the 9 th decade of life with abnormal behavior and focal seizures with MRI showing a right temporal T2 hyperintense non-enhancing lesion with electrographic evidence of right lateralized periodic discharges. CSF analysis and PCR for HSV-1 and 2 yielded negative results twice, and therefore acyclovir was discontinued. Patient initially improved following correction of hyponatremia. Patient however deteriorated and imaging revealed a new right parietal lesion. Third CSF sample showed lymphocytic pleocytosis with positive HSV-1 PCR. Patient improved following antiviral treatment. Discussion: Acyclovir treatment should continue in high clinical suspicion scenarios despite negative HSV PCR. We further discuss causes of PCR false negatives and challenges it poses for patient care. Abstract : Neuroscience; Nervous System; Viral Disease; Neurology; Diagnostics; neurovirology, MRI, infectious disease, EEG